Memorandum on the Implementation of a Unified School-on-the-Air (SOA) Program on Smart-Rice Agriculture in the Philippines - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The memorandum from Philippine Department of Agriculture recognized the manual of operations as the official guide of the national SOA program under Rice Competitiveness Enhancement Fund.